Wskazania dla mnichów w "Komentarzu do Modlitwy Pańskiej" w "Regule mistrza" - Czyżewski, Bogdan (Vox Patrum, 2018)
The annonymous work called The Rule of the Master, in the so-called Thema, contains a commentary to the Lord’s Prayer. The Master, in his interpretion of invocation, touches the Christian doctrine. He analyse adopted sonship, which men is receiving by the Grace of God. This grace is a fruit of salvation given by Christ passover. Every Christian receives this grace in sacrament of baptism. First three request in Lord’s Prayer, although directed to God strictly, also refer to bound between man and Father. These prayers contains double dimension: theocentric and antropocentric. First, these three request are leading to the God, and from Him, return to man to realize to him the obligations which are connected with the status: the child of God. Four next requests concer the specific needs of man, such as daily food, forgiveness, defense against the devil and temptations. We can not admit, that these four are focusing only on man. We can find in it also a deep theocentric feature. By directing these request to God, says The Master, man expect suport and help.